30 Blame rebalance fmri feedback proof-of-concept trial in major depressive disorder. Issue 8 (13th July 2017) - Zahn, R; Weingartner, J; Basilio, R; Bado, P; Mattos, P; Oliveira-Souza, Sato J de; Fontenelle, LF; Moll, J
Abstract : Objective: Using fMRI, we have identified lower coupling between anterior temporal (AT) and subgenual cingulate (SC) cortex while patients with major depressive disorder (MDD) experience guilt. This neural signature was detected despite symptom remission which suggests its role in MDD vulnerability. This double-blind, controlled, randomised and pre-registered clinical trial aimed at determining whether patients with MDD are able to voluntarily modulate this neural signature. To this end we developed an fMRI neurofeedback software tool (FRIEND), which measures AT-SC coupling and displays its levels to patients during fMRI in real time. Method: Twenty-eight patients with remitted MDD were randomised to two groups each receiving one session of fMRI neurofeedback whilst retrieving guilt and indignation-related autobiographical memories. They were instructed to feel the emotion whilst trying to increase the level of a thermometer-like display on a screen. Active intervention group: The thermometer levels increased with increasing levels of AT-SC correlations in the guilt condition. Control intervention group: The thermometer levels decreased when correlation levels deviated from the previous baseline level in the guilt condition thus reinforcing stable correlations. Both groups also received feedback during the indignation condition reinforcing stable correlations. Results: We confirmed our predictions that patients in the active intervention group are indeed able to increase the level of their AT-SC correlation for guilt vs. indignation after training compared to before training and that this differed significantly from the control intervention group. Conclusion: This provides the proof-of-concept for a novel MDD treatment approach. Future studies need to probe its efficacy when applied repeatedly.